The Effectiveness of the Implementation of Basic Tasks and Protocol Functions in Supporting Government Activities of Berau Regency - Katili, Rahmawati; Amin, Muh. Jamal; Sudirah, Sudirah (Technium Social Sciences Journal, 2021)
This article discusses the effectiveness of the primary tasks and functions of the protocol in supporting government activities in Berau Regency. This research method is a descriptive method with an inductive approach which describes in fact all the symptoms of problems that arise in the field and associated with relevant theories in order to get rational and general conclusions. The data sources of this research result from interviews with parties directly involved in protocol activities. Under the topic being carried out, this study uses Campbell’s (1989) effectiveness as a theoretical basis. The results show that the effectiveness of the major tasks and functions of the protocol in supporting government activities in the Berau Regency has been effective. This can see in the program’s success under Law No. 9 of 2010 concerning protocols, the success of the targets for carrying out leadership activities, satisfaction with the program known that leaders satisfied with protocol services, internal and external levels, namely at the internal level, the quality of human resources affects the quality of protocol activities and services, while the provision of incentives, leadership appreciation, leadership motivation, directions, and supporting facilities for the quality of performance needed to support the external level in achieving effective coordination and communication results, achieving the overall goal that the Berau Regency protocol objectives have been achieved although there are still shortcomings to improve human resource competencies.